2020
DOI: 10.1097/nur.0000000000000529
|View full text |Cite
|
Sign up to set email alerts
|

Child Abuse Response Simulation for Advanced Practice Nursing Students

Abstract: Purpose The purpose of this project was for advanced practice nursing students to gain experience taking a history from a parent or caregiver and communicating the treatment plan for an infant in which child abuse is suspected. Project Fifty-three students participated in a 1:1 simulated encounter with a standardized patient acting as the mother of an infant with a leg injury that reportedly resulted from a fall from the couch. Students received feedbac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 5 publications
2
11
0
Order By: Relevance
“…Adopting an interdisciplinary approach is crucial in the management of CAN [ 34 ], hence particular efforts were made to discuss the role of other health care professionals in the evaluation and management of CAN, including nursing staff and hospital and community social workers. Taking a detailed medical history while making sure that the described mechanism of injury is consistent with the child’s developmental stage and clinical status, performing a thorough clinical examination, requesting targeted laboratory and imaging studies and assessing them properly, identifying signs, symptoms and social indicators of CAN, recognizing the need for hospital admission, as well as making a referral to the investigative authorities when one’s level of suspicion is high are all necessary skills that healthcare students and professionals often report they lack [ 9 13 , 17 20 , 23 , 35 ] and that we, therefore, attempted to teach our workshop’s participants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adopting an interdisciplinary approach is crucial in the management of CAN [ 34 ], hence particular efforts were made to discuss the role of other health care professionals in the evaluation and management of CAN, including nursing staff and hospital and community social workers. Taking a detailed medical history while making sure that the described mechanism of injury is consistent with the child’s developmental stage and clinical status, performing a thorough clinical examination, requesting targeted laboratory and imaging studies and assessing them properly, identifying signs, symptoms and social indicators of CAN, recognizing the need for hospital admission, as well as making a referral to the investigative authorities when one’s level of suspicion is high are all necessary skills that healthcare students and professionals often report they lack [ 9 13 , 17 20 , 23 , 35 ] and that we, therefore, attempted to teach our workshop’s participants.…”
Section: Discussionmentioning
confidence: 99%
“…Teaching methods and educational interventions described in the literature mostly involve conventional didactic lectures [17][18][19][20][21], handing out protocols [15,18], decisional flow charts and selfinstructional kits with self-evaluation activities [20], case presentations and discussions with experts [15,18,21], direct participation in patient evaluation [21], videos [15,21] and audiotapes [19], e-learning modules [17,19,22], cards-illustrations and written scenarios [20] or virtual patients [19]. There is only one study describing a simulated encounter of nursing students with a person acting as the mother of an injured infant [23].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical simulations have been identified as another technique for improving recognition of child maltreatment as well as process and skill with reporting. Students found that the simulations prepared them for the high levels of emotional moral distress that may occur (McClure, Nelson, Anderson, Donnell, & Knox, 2020). After participating in a Child Abuse Reporting Interprofessional Simulation-Based Learning Experience (CAR-ISBE), 92% of participants reported greater comfort with both the needed interdisciplinary collaboration as well as recognition and reporting.…”
Section: Possible Interventions To Improve Recognitionmentioning
confidence: 99%
“…Nursing students and future professional nurses undergo clinical practice training and participate in patient care during their education (Subke et al, 2020). Although there are studies investigating nurses' knowledge and attitudes regarding child abuse (Bozkurt & Bağ, 2021; Elarousy & Abed, 2019; Lee & Kim, 2018), few studies have focused on nursing students (McClure et al, 2020; Özçevik et al, 2018; Turan, 2022). To the best of our knowledge, no study has investigated nursing students' attitudes toward reporting abuse and neglect in Turkey.…”
Section: Introductionmentioning
confidence: 99%